PENGARUH KUALITAS LAYANAN, MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO INDAH BORDIR DI SIDOARJO - Netta Try Pustika Sari; Mas Oetarjo; Mochamad Rizal Yulianto (Universitas Sarjanawiyata Tamansiswa, 2026)
The purpose of this study is to analyze the influence of service quality, brand, and price on purchasing decisions at Indah Bordir Shop in Sidoarjo. Increasing competition in the embroidery retail industry requires business actors to understand the main factors that drive consumer purchasing decisions in order to maintain competitiveness and customer loyalty. This research employs a quantitative approach using primary data collected through questionnaires distributed to 96 respondents who have previously purchased products from Indah Bordir Shop. The sampling technique used was purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS software, including instrument testing, classical assumption tests, and hypothesis testing through t-test and F-test. The results indicate that service quality, brand, and price each have a positive and significant effect on purchasing decisions. Service quality shows the strongest influence among the three variables, followed by brand and price. Simultaneously, all independent variables significantly affect purchasing decisions. These findings suggest that improving service quality, maintaining a strong brand image, and offering competitive pricing are essential strategies for enhancing consumer purchasing decisions at Indah Bordir Shop in Sidoarjo.